Conservation of functional domains involved in RNA binding and protein-protein interactions in human and Saccharomyces cerevisiae pre-mRNA splicing factor SF1. - Rain, J C (1998)
The modular structure of splicing factor SF1 is conserved from yeast to man and SF1 acts at early stages of spliceosome assembly in both organisms. The hnRNP K homology (KH) domain of human (h) SF1 is the major determinant for RNA binding and is essential for the activity of hSF1 in spliceosome assembly, supporting the view that binding of SF1 to RNA is essential for its function. Sequences N-terminal to the KH domain mediate the interaction between hSF1 and U2AF65, which binds to the polypyrimidine tract upstream of the 3' splice site. Moreover, yeast (y) SF1 interacts with Mud2p, the presumptive U2AF65 homologue in yeast, and the interaction domain is conserved in ySF1. The C-terminal degenerate RRMs in U2AF65 and Mud2p mediate the association with hSF1 and ySF1, respectively. Analysis of chimeric constructs of hSF1 and ySF indicates that the KH domain may serve a similar function in both systems, whereas sequences C-terminal to the KH domain are not exchangeable. Thus, these results argue for hSF1 and ySF1, as well as U2AF65 and Mud2p, being functional homologues.